ANALISIS KEMAMPUAN MAHASISWA PENDIDIKAN GURU SEKOLAH DASAR FKIP UNIVERSITAS RIAU DALAM PENGUKURAN KELILING DAN LUAS BANGUN DATAR - Zetra Hainul Putra (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2013)
The purpose of this study is to analyze student teachers at Primary School Teacher Education of Riau University in understanding the concepts of measurement of perimeter and area. The reason for conducting this research is that many student teachers usually use formal formulas in solving problems of perimeter and area measurement, and they tend to apply the same approach when teaching primary school students, causing students to not understand how the formulas work. Design research was chosen as the method for collecting data. The data were collected from 48 student teachers of the Primary School Teacher Education program at Riau University. The results showed that six out of ten groups of student teachers did not use partitioning at the beginning of the lesson and also made mistakes in measuring the perimeter of unstructured shapes. After classroom discussion, 96% of student teachers came to the idea of partitioning, which means they realized the importance of partitioning in measuring the area of unstructured shapes.